Pairing of homologous regions in the mouse genome is associated with transcription but not imprinting status. - Christel Krueger; Michelle R King; Felix Krueger; Miguel R Branco; Cameron S Osborne; Kathy K Niakan; Michael J Higgins; Wolf Reik (PLoS ONE)
Although somatic homologous pairing is common in Drosophila it is not generally observed in mammalian cells. However, a number of regions have recently been shown to come into close proximity with their homologous allele, and it has been proposed that pairing might be involved in the establishment or maintenance of monoallelic expression. Here, we investigate the pairing properties of various imprinted and non-imprinted regions in mouse tissues and ES cells. We find by allele-specific 4C-Seq and DNA FISH that the Kcnq1 imprinted region displays frequent pairing but that this is not dependent on monoallelic expression. We demonstrate that pairing involves larger chromosomal regions and that the two chromosome territories come close together. Frequent pairing is not associated with imprinted status or DNA repair, but is influenced by chromosomal location and transcription. We propose that homologous pairing is not exclusive to specialised regions or specific functional events, and speculate that it provides the cell with the opportunity of trans-allelic effects on gene regulation.